Proton Pump Inhibitors Usage Among Discharged Patients in a Tertiary Care Hospital- An Observational Study - Ahmed, Akhlak; Akter, Benojeer; Naby, Md Mahmudun; Rahman, Md Romanur; Hossain, Syed Zakir (Journal of Medicine, 2023)
Background: Proton pump inhibitors (PPI) have reportedly been used in inappropriate clinical settings, often leading to an increased risk of adverse effects, drug interactions, and costs. Aim: The aim of this study was to evaluate the appropriateness of PPI prescription on discharge of patients in medicine ward of a tertiary care hospital in Bangladesh. Methods: A cross-sectional study was done for 3 months in the department of medicine in a tertiary care hospital to evaluate the indications of PPI use, appropriateness of PPI use and types of PPI prescribed. A total of 107 patients who were prescribed PPI on discharge were enrolled after written informed consent and data were collected in a structured questionnaire. Results: Among the 107 patients discharged, 64 were males and 43 were females. The mean age was 51.3 ±17.6 (SD) years.Among the study population, 49 were appropriately prescribed PPI and 58 were inappropriately prescribed PPI. Regarding indications, 53.1% received PPI for prevention of anti-platelet induced gastric erosion and 18.9% were prescribed PPI for no apparent reason. Age (p=0.199) and gender (p=0.605) was not significantly associated with the appropriate prescription of PPI.Of the various preparations of PPI prescribed, esomeprazole was prescribed in most of the discharged patients (56%). Conclusion: this study demonstrates the existence of an over-prescription of PPI. PPI prescription needs to be improved, thereby reducing drug interactions, adverse effects and unnecessary economical expenses. J MEDICINE 2023; 24(2): 125-130